2020
DOI: 10.1109/access.2020.3004878
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Deformation of Pendant Drops on the Edge of High-Voltage Bushing Sheds Under Extreme Rainfall

Abstract: Flashover accidents on high-voltage bushings frequently occur under extreme rainfall, which is generally attributed to the bridging of adjacent sheds by pendant drops, a result of the dynamic deformation of pendant drops. We numerically investigate the effects of the parameters of pendant drops and the electric field on the dynamic deformation of pendant drops on a 500 kV transformer bushing under extreme rainfall and verify the simulation results by artificial rain experiment. The dynamic deformation of penda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Moreover, the reason for the sudden increase in Lwc in the process of large shed overhang rising, which is the speed of rainwater flowing to the edge of sheds, which increases as the overhang is from 105 mm to 120 mm, and the water droplets hanging on the shed edge have higher initial velocity, which leads to the significant increase in the length of water columns [28]. (2) Under different rainfall intensities, the trends of N wc , N wde , N wds and L wc with the change in large shed overhang are identical.…”
Section: Influence Of Large Shed Overhang On Parameters Of Surface Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the reason for the sudden increase in Lwc in the process of large shed overhang rising, which is the speed of rainwater flowing to the edge of sheds, which increases as the overhang is from 105 mm to 120 mm, and the water droplets hanging on the shed edge have higher initial velocity, which leads to the significant increase in the length of water columns [28]. (2) Under different rainfall intensities, the trends of N wc , N wde , N wds and L wc with the change in large shed overhang are identical.…”
Section: Influence Of Large Shed Overhang On Parameters Of Surface Ramentioning
confidence: 99%
“…Moreover, the reason for the sudden increase in Lwc in the process of large shed overhang rising, which is the speed of rainwater flowing to the edge of sheds, which increases as the overhang is from 105 mm to 120 mm, and the water droplets hanging on the shed edge have higher initial velocity, which leads to the significant increase in the length of water columns [28]. Moreover, the reason for the sudden increase in L wc in the process of large shed overhang rising, which is the speed of rainwater flowing to the edge of sheds, which increases as the overhang is from 105 mm to 120 mm, and the water droplets hanging on the shed edge have higher initial velocity, which leads to the significant increase in the length of water columns [28].…”
Section: Influence Of Large Shed Overhang On Parameters Of Surface Ramentioning
confidence: 99%
“…As mentioned above, the existence of these water-droplets is due to the good hydrophobicity of the materials. Previous studies have shown that the maximum electric field strength of the water-droplets on the upper shed appears at the interface between the liquid and the shed surface, where air is ionized [3][4][5][6][7][8][9][10][11][12][13][14]. These corona discharges did not further develop into an arc, because the shape of the water-droplets on the upper shed did not change significantly, resulting in no further distortion of the electric field intensity around the water-droplets.…”
Section: Discharge Characteristics and Flashover Processmentioning
confidence: 91%
“…In real applications, the whole post insulator is composed of several sections. It has been found that when the insulation height is less than 10m, the pollution flashover voltage of the post insulator increases linearly with the increase of insulation height [5][6][7][8][9][10][11][12][13][14][15]. Therefore, only one section of the entire insulator was used in this test to reduce the test voltage.…”
Section: Artificial Contamination Rain Flashover Testmentioning
confidence: 99%
See 1 more Smart Citation